1973
DOI: 10.1002/mrc.1270050404
|View full text |Cite
|
Sign up to set email alerts
|

1H‐NMR‐Spektroskopische Untersuchungen an methylsubstituierten Cyclohexen‐(4)‐dicarbonsäure‐(1,2)‐anhydriden

Abstract: Abstract-Chemical shifts and coupling constants of methyl substituted 4-cyclohexene-I ,2-dicarboxyJic anhydrides were determined. The NMR data demonstrate the boat conformation of the cis-anhydrides. The orientation of the cis-anhydride ring relative to the cyclohexene boat depends on the constitution and configuration of the compounds, and can be deduced from coupling constants and 6-values of the HI-and H,-protons. Methyl groups in the neighbourhood of these protons shift the resonance frequencies dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1975
1975
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…A detailed discussion of the conformations of 21 methylsubstituted cyclohexene-4,5-dicarboxylic acid anhydrides of type 102 was given. 317 For the trans compounds, only the rigid halfchair with diequatorial CO groups is possible. For the cis compounds, however, the large values found for 3J(H4, H5) of 9.4 to 10 Hz indicated that the respective CH bonds are eclipsed, and a boat geometry (102a) was proposed for the six-membered ring.…”
Section: Bicyclic and Tricyclic Systemsmentioning
confidence: 99%
“…A detailed discussion of the conformations of 21 methylsubstituted cyclohexene-4,5-dicarboxylic acid anhydrides of type 102 was given. 317 For the trans compounds, only the rigid halfchair with diequatorial CO groups is possible. For the cis compounds, however, the large values found for 3J(H4, H5) of 9.4 to 10 Hz indicated that the respective CH bonds are eclipsed, and a boat geometry (102a) was proposed for the six-membered ring.…”
Section: Bicyclic and Tricyclic Systemsmentioning
confidence: 99%
“…± Within the context of studies on the conformations of bicyclic anhydrides, the structure of cis-1,2,3,6-tetrahydrophthalic anhydride C 8 H 8 O 3 has been determined by X-ray diffraction [1]; its crystal structure consists of two symmetryindependent molecules per asymmetric unit. Their conformations are folded, both possessing a boat form for the cyclohexene ring, in agreement with experimental NMR solution data [2] [3]. Crystal packing of the two independent molecules in the unit cell has also been investigated [4], establishing non-bonded interactions of the dipoleÀdi-pole type between local electrical dipoles of the carbonyl groups CO ¥¥¥ CO. Concomitantly, several techniques of semi-empirical and ab initio molecular-orbital calculations have been applied for the determination of the molecular geometry of this compound and its isomers, 3,4,5,6-, 1,2,5,7-, and 1,4,5,6-tetrahydrophthalic anhydrides [5].…”
mentioning
confidence: 53%
“…The solvent was removed under reduced pressure. The anhydride was extracted into hexane and worked up as in the previous example to give cis- 1,2,3,6-tetrahydrophthalic anhydride ( 21 ) (0.026 g, 0.171 mmol, 84%) (identical to an authentic sample (Aldrich) by 1 H NMR comparison). Co II (salen) ( 6 ) (0.062 g, 0.191 mmol, 95%) was obtained by first treating the initially hexane-insoluble material with aqueous NaOH followed by the procedure outlined above.…”
Section: Methodsmentioning
confidence: 99%